Facile combustion synthesis of amorphous Al2O3-coated LiMn2O4 cathode materials for high-performance Li-ion batteries. (27th May 2021) - Liu, Honglei; Yang, Fangli; Guo, Junming; Xiang, Mingwu; Bai, Hongli; Wang, Rui; Su, Changwei
Abstract : The unique Al2 O3 -coating layer can suppress the Mn dissolution and resist HF corrosion, hence stabilizing the crystal structure of spinel LiMn2 O4 cathode materials. Abstract : Amorphous Al2 O3 -coated spinel LiMn2 O4 cathode materials were prepared via a simple combustion method at a low temperature using glucose as a fuel. The morphology and structure of all samples were characterized by X-ray diffraction (XRD) analysis and transmission electron microscopy (TEM). The thickness of the amorphous Al2 O3 -coating is about 5 nm. Moreover, the typical spinel structure of the LiMn2 O4 exhibits no change after coating Al2 O3 . Electrochemical characterization showed that the Al2 O3 -coating can improve the cycling and high current rate performance of the LiMn2 O4 ; in particular, the 1.0 wt% Al2 O3 -coated LiMn2 O4 cathode revealed a high initial discharge capacity of 120.4 mA h g −1 and a good cycling stability with a capacity retention of 93.52% after 100 cycles at 1 C. Moreover, an excellent high rate performance with an initial capacity of 84.2 mA h g −1 and a capacity retention of 76.96% after 1000 cycles are also obtained at 10 C.